Electron‐Transfer and Hydride‐Transfer Pathways in the Stoltz–Grubbs Reducing System (KOtBu/Et3SiH). (2nd October 2017) - Smith, Andrew J.; Young, Allan; Rohrbach, Simon; O'Connor, Erin F.; Allison, Mark; Wang, Hong‐Shuang; Poole, Darren L.; Tuttle, Tell; Murphy, John A.
Abstract: Recent studies by Stoltz, Grubbs et al. have shown that triethylsilane and potassium tert ‐butoxide react to form a highly attractive and versatile system that shows (reversible) silylation of arenes and heteroarenes as well as reductive cleavage of C−O bonds in aryl ethers and C−S bonds in aryl thioethers. Their extensive mechanistic studies indicate a complex network of reactions with a number of possible intermediates and mechanisms, but their reactions likely feature silyl radicals undergoing addition reactions and SH 2 reactions. This paper focuses on the same system, but through computational and experimental studies, reports complementary facets of its chemistry based on a) single‐electron transfer (SET), and b) hydride delivery reactions to arenes.